Influence of the Ni/Co Mass Ratio on the Microstructure and Properties of Quaternary Cu-Ni-Co-Si Alloys - Li, Jiang (Materials (Basel), 2019)
The properties and microstructural evolution of quaternary Cu-Ni-Co-Si alloys with different Ni/Co mass ratios are investigated systematically. These alloys exhibit higher mechanical properties when the Ni/Co mass ratio is 1.12-1.95 (NC-4-NC-5) and show excellent electrical conductivity when the Ni/Co mass ratio is 0.05-0.5 (NC-1-NC-3). With an increase in the Ni/Co ratio, the dimension of precipitated phase continues to increase and the grain size also visibly grows and coarsens. At the same time, the precipitation process of the NC-5 alloy is the most adequate, resulting in the highest mechanical properties. In addition, the precipitated phase in the alloys was confirmed to be the (Ni, Co)(2)Si composite phase. The number of Ni(2)Si phases in the precipitated phase gradually increased, and the Ni atoms exhibited the strongest co-segregation alongside the increasing Ni/Co ratio. Compared with the alloy without a Co element, the addition of Co helped refine the grain size and accelerate the precipitation of the particle phase and purify solute atoms in the matrix, thereby simultaneously improving mechanical properties and conductivity. The present work provides a new method for the development of multicomponent Cu-Ni-Si-Co-X alloys with outstanding comprehensive performance.